The Impact of Ectoparasites on Morphometric Profiles of Hotate Scallop In Funka Bay, Hokkaido, Japan - Faizah, Farkhah Nur; Syakuri, Hamdan; Sanjayasari, Dyahruri; Imlami, Ainulyakin Hasan (Fakultas Perikanan dan Ilmu Kelautan, 2025)
The hotate clam (Mizuhopecten yessoensis) is one of the clam species that lives in cold-temperature waters with the largest production in the Japanese region. However, the sustainability of this aquaculture is threatened by various factors, including ectoparasite infections that can affect the morphometric profile of the scallop. This study aimed to analyze the impact of ectoparasites on the morphometry of hotate clams in Funka Bay, Hokkaido, and to inventory the types of ectoparasites found. Samples of 25 individual hotate mussels were taken using random sampling techniques and morphometric measurements were taken using Image-J software. Ectoparasite infestation was categorized into four categories: free, low, medium and high. Analysis was conducted using One-Way ANOVA and Fisher's Pairwise Comparison follow-up test (P<0.05), as well as hierarchical cluster analysis based on the Bray-curtis similarity index visualized in a dendrogram. The results showed that there were two types of ectoparasites, namely Polydora sp. and Barnacles sp., with the dominance of Polydora sp. which was found in 17 individuals. Some morphometric distances such as AD, AE, BD, and CE showed significant differences between infestation categories. The dendrogram showed that the 'free', 'low', and 'medium' categories had high morphometric similarity (0.987), while the 'high' category showed lower similarity (0.96).